2017
DOI: 10.18632/oncotarget.19947
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin-induced miR-21 promotes mitochondrial homeostasis and adaptation in mTORC1 activated cells

Abstract: mTORC1 hyperactivation drives the multi-organ hamartomatous disease tuberous sclerosis complex (TSC). Rapamycin inhibits mTORC1, inducing partial tumor responses; however, the tumors regrow following treatment cessation. We discovered that the oncogenic miRNA, miR-21, is increased in Tsc2-deficient cells and, surprisingly, further increased by rapamycin. To determine the impact of miR-21 in TSC, we inhibited miR-21 in vitro. miR-21 inhibition significantly repressed the tumorigenic potential of Tsc2-deficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 44 publications
(41 reference statements)
1
17
0
Order By: Relevance
“…In cardiac tissue, miR21 has been shown to directly promote mitochondrial cytochrome B translation and reduce reactive oxygen species production . Additionally, miR21 promotes mitochondrial homeostasis and adaptation in mTORc1‐activated cells . Further, miR21 promotes cancer cell‐survival by down‐regulating PTEN and consequently activating the PI3K/AKT/mTOR pathway .…”
Section: Discussionmentioning
confidence: 99%
“…In cardiac tissue, miR21 has been shown to directly promote mitochondrial cytochrome B translation and reduce reactive oxygen species production . Additionally, miR21 promotes mitochondrial homeostasis and adaptation in mTORc1‐activated cells . Further, miR21 promotes cancer cell‐survival by down‐regulating PTEN and consequently activating the PI3K/AKT/mTOR pathway .…”
Section: Discussionmentioning
confidence: 99%
“…Changes in miRNA profiling are implicated in various human diseases such as LAM (18,19). However, whether miRNAs contribute to LAM therapy remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, direct measurements showed that the combination of rapamycin and miR-21 inhibition reduced mitochondrial content, mitochondrial membrane potential, as well as, overall mitochondrial function. More excitingly, this combined treatment significantly reduced in vivo growth of xenograft tumors and increased survival in mice by four-fold [7].…”
Section: Synergistic Treatment Of Ts Aditi U Gurkar and Toren Finkelmentioning
confidence: 95%
“…al. tested the hypothesis that miR-21 upregulation might help protect TSC2-deficient cells from the cytotoxic effects of mTORC1 inhibition [7]. Interestingly, the authors found that miR-21 is upregulated in TSC2-deficient cells (characterized by high mTORC1 activity) and further induced upon rapamycin treatment (a potent inhibitor of mTORC1).…”
Section: Synergistic Treatment Of Ts Aditi U Gurkar and Toren Finkelmentioning
confidence: 99%